2023
DOI: 10.1007/s15010-022-01960-2
|View full text |Cite
|
Sign up to set email alerts
|

The clinical spectrum of aspergillosis in chronic obstructive pulmonary disease

Abstract: Chronic obstructive pulmonary disease (COPD) is the third leading cause of death worldwide. In this review, we present the clinical spectrum and pathogenesis of syndromes caused by Aspergillus in COPD namely invasive aspergillosis (IA), community-acquired Aspergillus pneumonia, chronic pulmonary Aspergillosis and Aspergillus sensitisation. Some of these entities are clearly linked to COPD, while others may coexist, but are less clearly liked directly to COPD. We discuss current uncertainties as these pertain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 150 publications
0
9
0
8
Order By: Relevance
“…1 In recent years, it has become an increasingly important global public health concern. 1,2 As per the recommendations by the European Confederation of Medical Mycology (ECMM), indicators for monitoring CPA include imaging assessment, culture from respiratory samples, and serology on Aspergillus-specific IgG. 3 Some studies, on the other hand, suggested only a weak correlation between serology finding and CPA treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In recent years, it has become an increasingly important global public health concern. 1,2 As per the recommendations by the European Confederation of Medical Mycology (ECMM), indicators for monitoring CPA include imaging assessment, culture from respiratory samples, and serology on Aspergillus-specific IgG. 3 Some studies, on the other hand, suggested only a weak correlation between serology finding and CPA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pulmonary aspergillosis (CPA) is a progressive respiratory syndrome predominantly affecting individuals who are immunocompetent or subtly immunocompromised, particularly those with underlying structural lung diseases, most notably post‐treatment tuberculosis (TB) 1 . In recent years, it has become an increasingly important global public health concern 1,2 . As per the recommendations by the European Confederation of Medical Mycology (ECMM), indicators for monitoring CPA include imaging assessment, culture from respiratory samples, and serology on Aspergillus ‐specific IgG 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis and identification of factors predisposing to pulmonary aspergillosis are therefore critical to reduce mortality from fungal infections. 4 Ascaris spp. induce immunological and structural changes in the lungs during larval migration owing to the switch to Th2 from Th1 response.…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis and identification of factors predisposing to pulmonary aspergillosis are therefore critical to reduce mortality from fungal infections. 4…”
Section: Introductionmentioning
confidence: 99%
“…A study in 2017 reported global estimates of 3,000,000 cases of chronic pulmonary aspergillosis, and ~ 250,000 cases of invasive aspergillosis [4]. The immunocompromised hosts, such as those with haematological malignancies, solid organ transplants, and chronic lung diseases, and those exposed to environmental triggers such as dust and mould, are disproportionately affected by aspergillosis [5].…”
Section: Introductionmentioning
confidence: 99%